Active Role of the Library in the process of Democratic Learning - Banek, Mihaela (Array, 2001)
The role of public library in post communist countries and countries in transition does not stop with the basic library functions (book loans, children sector etc.) but its role has become more responsible as well as complex. In last few years, Croatian people, bombed by the media, are being confronted with new political terminology. What is that thing called "democracy", what does it mean to have a "right to elect", what kind of society is "open society", what kind of society are we living in? These are only some frequently asked questions that ordinary Croatian citizen is looking to find an answer on. Schools, newspapers and television (mass media) are no longer enough in the process of education. Public library has to take over the role of an educator that will guide users through "secret political terminology" and enable them to take an active role in political life of their community. In the public Libraries of Zagreb and Zadar we wanted to see users' opinion about the library as democracy learning place so we exhibited books about democracy, totalitarism, political processes, etc. We were interested in finding out if users recognize library as a place where information of political context can be find.